Male circumcision, sexual behavior, and HIV status in Uganda - Kibira, Simon P.S.; Nansubuga, Elizabeth; Tumwesigye, Nazarius M. (DHS Working Papers No. 100, 2013)
After a series of studies that revealed the protective effect of male circumcision against HIV infection, WHO/UNAIDS in 2007 recommended the adoption of safe male circumcision as one of the effective strategies in reducing heterosexually acquired HIV. To this effect, in 2010 the Ministry of Health in Uganda developed a circumcision policy, and circumcision was added to the strategy of abstinence, being faithful, and condom use (ABC) to protect against AIDS. Especially after the implementation of the safe male circumcision (SMC) policy, however, there has been a concern that some circumcised men may lead a more risky sexual lifestyle than non- circumcised men. This paper, therefore, examines the associations am ong circumcision status, age at circumcision, risky sexual behavi ors, and HIV serostatus among men.